Lie symmetry analysis of two dimensional weakly singular integral equations - Pashayi, S.; Shahmorad, S.; Hashemi, M. S.; İnç, Mustafa (Elsevier, 2021)
In this paper, symmetry groups of a two-dimensional weakly singular integral equation are discussed. A new method is proposed for the prolongation formula of the given equations. Using the introduced prolongation formula, we derive the symmetry groups and invariant solutions of the above-mentioned weakly singular integral equation wherever possible. In order to solve the extracted determining equation, a special approach is proposed. The symmetry groups for different types of the free terms are presented. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Symmetry groups; Weakly singular integral equation; Infinitesimal generator; Prolongation